Isolated endogenous Fusarium endophthalmitis in an immunocompetent adult after a thorn prick to the hand - Milligan, Alice L. (Am J Ophthalmol Case Rep, 2016)
PURPOSE: To report the case of an immunocompetent adult presenting with endogenous Fusarium endophthalmitis. OBSERVATIONS: A woman in her thirties presented with symptoms and signs of a unilateral anterior uveitis. After initial improvement with topical corticosteroids, she continued to develop a panuveitis with an associated drop in vision to counting fingers. A vitreous biopsy confirmed Fusarium solani by 18S rRNA fungal gene detection and PCR sequencing. Despite treatment with pars plana vitrectomy, intravitreal amphotericin B and systemic voriconazole her visual outcome was poor. Detailed review of her antecedent history revealed the route of acquisition to be a thorn prick to the hand two weeks prior to presentation. CONCLUSIONS AND IMPORTANCE: This patient's endophthalmitis most likely resulted from cutaneous inoculation of Fusarium solani with subsequent hematogenous spread. Endogenous Fusarium endophthalmitis is well recognized in the immunocompromised but is very rarely seen in the immunocompetent. This case highlights the importance of thorough history-taking and consideration of fungal endophthalmitis in the differential diagnosis of a treatment-refractory uveitis.